EDUKASI AKUNTANSI DIGITAL MELALUI APLIKASI AKUNTANSIKU PADA UMKM CV ASA MANDIRI & PT GESANG SEMPULUR MIGUNANI - Ramadhani, Berlian Amalia (LPPM ITB AAS Indonesia Surakarta, 2024)
Financial reports play a vital role in a business as they are used to record all expenses and revenues. Additionally, financial reports serve to determine the extent of profit or earnings obtained. These financial reports serve as the foundation for crafting strategies and making business-related decisions. The aim of this activity is to provide training and guidance on financial transaction recording for CV Asa Mandiri and PT Gesang Sempulur Migunani. Currently, these small and medium-sized enterprises (UMKM) manually record their financial transactions, and they blend personal and company finances, making it challenging for business owners to ascertain their profits. This difficulty arises from the owners' limited understanding of the fundamental principles of financial transaction recording and the significance of financial reporting. Hence, this training and mentoring activity is being carried out to assist CV Asa Mandiri and PT Gesang Sempulur Migunani in enhancing their financial transaction recording practices. Keywords: Financial Reports, Training, Assistance, UMKM